POSITIVE INFLUENCE OF ARTICHOKE EXTRACT ON STRUCTURAL AND METABOLIC PROCESSES IN BONE TISSUE OF RATS CONDITIONED UPON CADMIUM-NITRIC INTOXICATION - Khopta, N.S.; Shpilchak, L.Ya. (World of Medicine and Biology, 2019)
The purpose of the study was to investigate the changes in the histological structure, bioelement compositionand markers of bone metabolism in the blood of white male rats with experimental cadmium-nitrite intoxication and the use of artichoke extract for correction of disturbances that arose under the influence of toxicants. It has been established that on the background of combined action of CdCl2and NaNO2in animal femoral bones, osteoclastic resorption processes over osteosynthesis predominate and ash content of the most important osteotropic elements (Ca, Zn and Cu significantly decrease), while cadmium content increases greatly. Indicators of phosphorous-calcium metabolism change in blood plasma, the activity of acid phosphatase increases and oxyproline concentration increases, alkaline phosphatase activity decreases. Artichoke extract positively influences on reparative processes in bones. With the administration of artichoke extract the balance of macro- and micronutrients is restored in the femur of the animals, cadmium is significantly reduced. Biochemical markers of bone metabolism are normal in the blood plasma, the values of which do not significantly differ from those of intact ones (with the exception of the concentration of oxyproline that remains higher) to the end of the experiment.
Keywords: artichoke extract; cadmium-nitrite intoxication; histological structure of femoral bones; markers of bone metabolism